Enhancing decellularized vascular scaffolds with PVDF and PCL reinforcement: a fused deposition modeling approach - Klyshnikov, Kirill Yu.; Rezvova, Maria A.; Belikov, Nikita V.; Glushkova, Tatiana V.; Ovcharenko, Evgeny A. (Frontiers in Cardiovascular Medicine, 2023)
Background Decellularized xenogenic scaffolds represent a promising substrate for tissue-engineered vascular prostheses, particularly those with smaller diameters (<6 mm). Despite their benefits, a notable limitation presents itself during decellularization, namely, the diminished mechanical strength that introduces the risk of aneurysmal dilations in the early post-implantation period. This study introduces a strategy for modification the mechanical properties of these biological scaffolds through the forming of an external polymeric reinforcement via thermal extrusion. Methods The study utilized scaffolds fabricated from bovine internal mammary arteries through decellularization and preservation. The scaffolds were divided into subgroups and reinforced with polymeric helices made of Polyvinylidene fluoride (PVDF) and Polycaprolactone (PCL), n = 5 for each. An experimental setup for external reinforcement coating was designed. Computed microtomography was employed to obtain accurate 3D models of the scaffolds. Mechanical properties were evaluated through in vitro uniaxial tension tests (Z50, Zwick/Roell, Germany), compliance evaluation and numerical simulations (Abaqus/CAE, Dassault Systemes, France) to investigate the effect of external reinforcement on aneurysm growth. Results Using a double-layer helix for the reinforcement significantly enhanced the radial tensile strength of the scaffolds, increasing it up to 2.26 times. Yet, the comparison of vessel's compliance between two reinforced and the Control scaffolds within the physiological pressures range did not reveal any significant differences. Numerical simulation of aneurysm growth showed that thin-walled regions of the Control scaffold developed aneurysmal-type protrusions, bulging up to 0.7 mm, with a substantial degradation of mechanical properties. In contrast, both PVDF and PCL reinforced scaffolds did not exhibit significant property degradation, with deformations ranging 0.1–0.13 mm depending on the model, and a maximum decrease in the modulus of elasticity of 23%. Conclusion The results of the study demonstrated that the external polymer helical reinforcement of decellularized scaffolds via thermal extrusion enables a controlled modification of mechanical properties, notably enhancing radial strength while maintaining sufficient compliance within the physiological pressure range. A series of in vitro tests demonstrated the consistency and potential of this approach for decellularized xenogenic scaffolds, a concept that had not been explored before.